IMMUNOLOGICAL RESPONSE CHARACTERISTICS IN INDIVIDUALS WITH OVERLAPPING BRONCHIAL ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Raufov Alisher Anvarovich (Bright Mind Publishing, 2025)
This study addresses the immunological characteristics of patients with asthma, COPD, and their overlap (ACO). A correlation analysis involving ten clinical and immunological indicators was performed, and based on the relationship between IL-8 and IFN-γ, a prognostic index was developed to assess the likely course of bronchial asthma and COPD overlap. This index enables prediction of disease progression and supports the selection of appropriate therapeutic strategies.
Keywords: BA, COPD, ACO, cytokines, IgE, correlation analysis.